Analisis Pendapatan Usaha Penggemukan Ternak Domba Wonosobo (Dombos) Periode Bulan November 2022- Januari 2023 Di Peternakan Griya Ternak Farm Wonosobo: Analysis Business Income Wonosobo Sheep Fattening (Dombos) Period November 2022-January 2023 At Griya Livestock Farm Wonosobo Farm (Jurnal Riset Agribisnis dan Peternakan, 2024)
The study was conducted at the Griya Ternak Farm Wonosobo sheep farming firm in May 2023. The public will be informed by this research about production costs, revenues, income, profits, and factors influencing income. The findings of this study show that the Wonosobo sheep farming company, Griya Ternak Farm Wonosobo, made IDR 97,995,800 in revenue between November 2022 and January 2023. The variables that affect the revenue of the Wonosobo sheep fattening company, at Griya Ternak Farm Wonosobo, are revenue, variable costs, and the weight of the harvested sheep.
Keywords: Wonosobo Sheep; Costs; Income; Profits